The Role of Sports in Promoting Social Inclusion and Health in Marginalized Communities - Karstensen , Valerie; Piskorz-Ryń , Oriana; Karna , Wioleta; Lee , Angel; Neo , Xian Seng; Gottschlich, Daniela (International Journal of Sport Studies for Health, 2024)
Objective: This study aims to explore the role of sports in promoting social inclusion and health within marginalized communities.Methods and Materials: A qualitative research design was employed, utilizing semi-structured interviews to gather in-depth insights from participants. Individuals from various marginalized communities, including ethnic minorities, low-income groups, and those with disabilities, were purposefully sampled. Data collection continued until theoretical saturation was achieved, with interviews being transcribed verbatim and analyzed using NVivo software. A thematic analysis approach was used to identify and categorize recurring themes and patterns in the data.Results: The study identified three main themes: social inclusion, health and well-being, and personal development and growth. Participants reported that sports participation significantly enhanced their social networks, community cohesion, and broke down social barriers, fostering a sense of belonging and empowerment. Physical health benefits included improved fitness and reduced chronic diseases, while mental health improvements encompassed stress relief, anxiety reduction, and mood enhancement. Sports also facilitated personal development by fostering leadership skills, teamwork, and providing educational and career opportunities.Conclusion: Sports play a crucial role in promoting social inclusion and health within marginalized communities. The findings underscore the multifaceted benefits of sports participation, including enhanced social connections, improved physical and mental health, and personal empowerment. The study suggests that increasing access to inclusive sports programs and addressing barriers to participation can further amplify these benefits.